Perspectives on democratic consolidation in Southern Africa: the five general elections of 2004 - Lemon, A (Elsevier, 2007)
Huntingdon's 'third wave' of democracy came late to Africa, but five countries held general elections in 2004, providing an opportunity to reflect on degrees of democratic consolidation in the region. African political dynamics are considered in relation to the political and economic environment together with national, ethnic and regional identities and the way in which these may influence democratic consolidation. The electoral systems of the five countries are considered in relation to the dominant party effect. The course and outcomes of the five elections are examined in relation to indicators of participation and competition suggested by Lindberg. The latter's indicators of legitimacy are considered in relation to more detailed analysis of each election in its national context, paying attention to the influence of ethnic, regional and other divisions on outcomes, which are mapped. Major procedural flaws prevented democratic consolidation in Mozambique and hindered it in Malawi, where the party system also proved unstable. South Africa, Namibia and Botswana satisfied most of the criteria apart from turnover and provide convincing evidence of the institutionalisation and acceptance of democracy, albeit qualified by the continuing dominance of their governing parties. In all five countries the equation of democracy with socio-economic benefits threatens disillusionment in the face of poverty and inequality.